Perceção dos enfermeiros de cuidados paliativos sobre a intervenção do enfermeiro especialista em enfermagem de reabilitação - Martins, Rosa (2020)
Introduction: Palliative Care is demanding and humanized care that aims to maximize the quality of life and dignity of the Person. For the same purpose, rehabilitation nurses intervene in specialized care. Objective: Thus, it was intended to know the nurses' perception about the interventions of specialized nurses in rehabilitation nursing in Palliative Patients. Methods: Qualitative study, using content analysis. The sample consisted of 13 nurses, (12 female and 1 male). They were all licensed in nursing and exercised their professional activity in Palliative Care Units. For data collection, a semi-structured interview was used. Results: The participants present very positive perceptions about the specialized care of the rehabilitation nurses, considering them as facilitating agents in meeting the patient's needs. The most prominent interventions in the pursuit of the patient's well-being were mobilization, respiratory kinesitherapy, deglutition / dysphagia training, massage and preservation of autonomy and independence. Conclusion: Nurses 'perception of the intervention of the Rehabilitation Specialist Nurse in people hospitalized in PC units is positive, emphasizing the maintenance of the patients' functional capacities, prevention of complications and reduction of disabilities, however the visibility by peers is still insipid.